A proposal for systematic monitoring of the commercial determinants of health: a pilot study assessing the feasibility of monitoring lobbying and political donations in Australia - Jennifer Lacy-Nichols; Katherine Cullerton (BMC, 2023)
Abstract Background The commercial determinants of health include a range of practices to promote business interests, often at the expense of public health. Corporate political practices, such as lobbying and campaign donations, are used to influence policy makers and foster a political and regulatory environment conducive to business interests. Despite recognition of their public health importance, thus far there are relatively few efforts to systematically monitor commercial political practices. Methods A pilot study was conducted to explore the feasibility of systematically monitoring two political practices - lobbying and political contributions - for 'harmful industries' (alcohol, gambling, ultra-processed food and tobacco industries) in Australia. Potential data sources were reviewed to compare data availability and detail. Two publicly available datasets were selected for the pilot: ministerial diaries for New South Wales and annual donor filings from the Australian Electoral Commission. Google Data Studio was used to analyse and visualise findings.  Results The pilot study resulted in the creation of several interactive charts and dashboards that supported analysis and interrogation of the data. These charts helped to easily convey the volume of lobbying and political donations, as well as changes over time. For example, we found that between July 2014 and December 2020, NSW ministers had 20,607 meetings, of which 634 meetings were with harmful industries. And between 1998 and 2020, a total of $576,519,472 disclosed donations were made to political parties and other entities, of which $35,823,937 were from harmful industries. Conclusions Opportunities to develop a program to monitor commercial political practices face several challenges including access barriers arising from poor availability and detail of data, technical barriers arising from the format of data disclosures and coding challenges arising from the diverse nature of the commercial sector. Despite these challenges, our pilot study demonstrates the potential to implement a monitoring program and to expand its scope to other commercial determinants of health.